Harmonisation of Legal Rules on Chemical Castration as a Lex Specialist Based on The Principle of Legality in The Perspective of Criminal Law - Hermawanti, Kori (Yayasan Studi Cendekia Indonesia (YSCI), 2024)
Conflicts between several legal regulations and the existence of a legal vacuum make it problematic that chemical castration can be implemented, especially in Article 66 paragraph (1) of Law no. 1 of 2023 does not yet accommodate the implementation of chemical castration as an additional crime, so there is a need for changes and harmonisation of related legal regulations. The method used in this research is a qualitative method. The application of police medicine as an alternative to the execution of chemical castration has not yet received definite legality regarding the procedures and other rules for carrying out chemical castration in the police environment. In the implementation of chemical castration in Indonesia there are still several things that need to be clarified, especially for those carrying out the duties or executors. The existence of overlapping policies requires that efforts be made to harmonise both the health law perspective, medical practice, medical ethical code, human rights perspective, and also based on the Indonesian Criminal Code, and derivative legal regulations that must be harmonised.